Formic Acid to Power towards Low‐Carbon Economy. Issue 15 (23rd February 2022) - Dutta, Indranil; Chatterjee, Sudipta; Cheng, Hongfei; Parsapur, Rajesh Kumar; Liu, Zhaolin; Li, Zibiao; Ye, Enyi; Kawanami, Hajime; Low, Jonathan Sze Choong; Lai, Zhiping; Loh, Xian Jun; Huang, Kuo‐Wei
Abstract: The storage and utilization of low‐carbon electricity and decarbonization of transportation are essential components for the future energy transition into a low‐carbon economy. While hydrogen has been identified as a potential energy carrier, the lack of viable technologies for safe and efficient storage and transportation of H2 greatly limits its applications and deployment at scale. Formic acid (FA) is considered one of the promising H2 energy carriers because of its high volumetric H2 storage capacity of 53 g H2 /L, and relatively low toxicity and flammability for convenient and low‐cost storage and transportation. FA can be employed to generate electricity either in direct FA fuel cells (FCs) or indirectly as an H2 source for hydrogen FCs. FA can enable large‐scale chemical H2 storage to eliminate energy‐intensive and expensive processes for H2 liquefaction and compression and thus to achieve higher efficiency and broader utilization. This perspective summarizes recent advances in catalyst development for selective dehydrogenation of FA and high‐pressure H2 production. The advantages and limitations of FA‐to‐power options are highlighted. Existing life cycle assessment (LCA) and economic analysis studies are reviewed to discuss the feasibility and future potential of FA as a fuel. Abstract : The utilization of low‐carbon electricity and decarbonization of transportation are essential to a low‐carbon economy. Hydrogen has been identified as an energy carrier, but the lack of viable storage and distribution technologies greatly limits its uses. A chemical hydrogen storage system powered by formic acid can replace energy‐intensive liquefaction and compression processes for hydrogen, enabling higher efficiency and broader applications.